Analytical modeling, experimental investigation and applications of stimulated Brillouin scattering in optical fibers - Al-Asadi, Hamid Ali Abed (2011)
In the work presented in this dissertation, the generation of stimulated Brillouin scattering (SBS) and its applications in optical fibres are theoretically and experimentally investigated. The initial work is concerned with the investigation of SBS threshold power reduction techniques. The method under study is namely a pump recycling technique in which the residual pump power is recycled back to act as the secondary pump. A new mathematical model was developed for the proposed technique. The results obtained from this model compare favorably with the experimental results. The pump recycling technique can reduce the SBS threshold by around 50% as compared to the one obtained from the conventional technique. The threshold exponential gain of SBS is very critical in determining the performance of the Stokes signal. Particle swarm optimization (PSO) is utilized to optimize this parameter. The simulation results obtained from the PSO model are compared with two other established models: the localized, non-fluctuating source model and the distributed (non-localized) fluctuating source model. For the PSO model, the threshold exponential gain increases from 15.9 to 17.4 from 5 to 1 km respectively. The threshold exponential gain for long fibers (L > 5 km) is gradually decreased and close to 14.6. Theoretical models of the Brillouin fiber laser in a ring cavity were also developed. Even though the Stokes laser is designed to propagate unidirectionally along the optical fibre, the second-order Stokes signal can also be produced when the SBS threshold condition is satisfied. Even though this second-order Stokes signal cannot make a complete round trip because of the isolation provided by the circulator, it affects the amplification of the first-order Stokes signal. This influence has been considered in the development of the theoretical model. An optimum operating point is determined in order to obtain an acceptable output power with only 10% of the power transferred from the first-order Stokes signal to the second-order Stokes signal.A theoretical model of a double-Brillouin-frequency shifter (DBFS) is demonstrated to achieve a double-spacing Stokes signal. Evidence of the higher-order Stokes signal generation becomes the foundation of the theoretical model development of DBFS. For the proposed structure, the 4-port circulator is used to isolate the propagation of odd- and even-order Stokes signal in a ring cavity structure. Although the proposed double- Brillouin-frequency shifter is able to generate the second-order Stokes signal, it also suffers from producing higher-order Stokes waves. Therefore, the developed theoretical model includes the Stokes wave interaction up to its fourth order. The analysis of sidemode suppression ratio can be achieved because the proposed DBFS allows the propagation of the remaining Brillouin pump and higher even-order Stokes signal. There is an optimum Brillouin pump power to achieve a maximum side-mode suppression ratio.